SOLUSI DALAM MENEKAN TINGKAT KEMISKINAN (SUATU ANALISA SOSIOLOGI EKONOMI ISLAM) - Alimin, Dr (JURIS (Jurnal Ilmiah Syariah), 2010)
How can humans live happily is old problems and new problems as well, he is also the problem of micro and macro issues from of the economics perspective. There is no way to be able to live happily except by getting rid of the three enemies of man, namely poverty, ignorance and disease. In terms of social factors, poverty is also a chain where the chain can be broken. It is an interesting phenomenon to listen to the history of Islam that explains that the first holy war undertaken by Abu Bakr was the war against poverty in the form of warfare against the rich who do not want to pay the zakat that should be enjoyed directly to the poor. This paper explores the problems or social problems as an inspiration or a solution to the problem of poverty in the Islamic perspective.